X-ray study of the density distribution of FFF-printed samples with different fill patterns; Journal of Instrumentation; Vol. 19, June 2024, iss. 6 : The XIV International Symposium on Radiation from Relativistic Electrons in Periodic Structures merged with the VIII International Conference on Electron, Positron, Neutron and X-ray Scattering under External Influences, RREPS-23 & Meghri-23, 18-22 September, 2023 Tsaghkadzor, Republic of Armenia - Bulavskaya A. A. Angelina Aleksandrovna; Bushmina E. A. Elizaveta Alekseevna; Grigorieva (Grigorjeva) A. A. Anna Anatoljevna; Miloichikova I. A. Irina Alekseevna; Stuchebrov S. G. Sergey Gennadevich (2024, 2024)
Title screen